Antioxidants in Greek Virgin Olive Oils - Kalogeropoulos, Nick (Antioxidants (Basel), 2014)
Greece is ranked third after Spain and Italy in virgin olive oil production. The number of Greek olive cultivars—excluding clonal selections—is greater than 40; however, more than 90% of the acreage is cultivated with 20 cultivars, adapted to a wide range of environmental conditions. Greek virgin olive oils, produced mainly with traditional, non-intensive cultivation practices, are mostly of exceptional quality. The benefits of consuming virgin olive oil, originally attributed to its high oleic acid content, are now considered to be the combined result of several nutrient and non-nutrient phytochemicals. The present work summarizes available data regarding natural antioxidants in Greek virgin olive oils (VOO) namely, polar phenolic compounds, tocopherols, squalene, and triterpenic acids. The literature survey indicated gaps in information, which should be filled in the near future so that the intrinsic properties of this major agricultural product of Greece will be substantiated on a solid scientific basis.